1986
DOI: 10.1246/bcsj.59.3179
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Lipids. XIV. Inhibition of Oxidation of Methyl Linoleate by Fatty Acid Esters of l-Ascorbic Acid

Abstract: Various kinds of fatty acid esters of l-ascorbic acid were synthesized and their role as chain-breaking antioxidant was studied in the oxidation of methyl linoleate in homogeneous solution. Fatty acid esters of ascorbic acid at either 6- or both 5- and 6-positions were effective as antioxidant and suppressed the oxidation of methyl linoleate, whereas those having ester group at 2-position did not act as antioxidant. 5,6-Erythorbyl dipalmitate was also effective as an antioxidant. Ascorbic acid esters inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…65 times more reactive as an oxidation inhibitor for linoleic acid than the hydrophilic ascorbic acid in SDS micelles, despite the fact that they showed similar reactivity in homogeneous solution [91]. A similar effect of the side-chain of vitamin E analogues on the antioxidation efficiency in SDS has been reported most recently by Castle and Perkins [104], who suggested that intermicellar diffusion may be the ratelimiting step of the antioxidation.…”
Section: Antioxidant Synergism Of Vitamin C and Vitamin Esupporting
confidence: 70%
See 1 more Smart Citation
“…65 times more reactive as an oxidation inhibitor for linoleic acid than the hydrophilic ascorbic acid in SDS micelles, despite the fact that they showed similar reactivity in homogeneous solution [91]. A similar effect of the side-chain of vitamin E analogues on the antioxidation efficiency in SDS has been reported most recently by Castle and Perkins [104], who suggested that intermicellar diffusion may be the ratelimiting step of the antioxidation.…”
Section: Antioxidant Synergism Of Vitamin C and Vitamin Esupporting
confidence: 70%
“…Furthermore, vitamin E remained almost intact and only vitamin C was consumed at the initial stage of oxidation and vitamin E was consumed only after vitamin C was exhausted. It confirmed that the peroxy radical was trapped by vitamin E and the resulting vitamin E radical was regenerated by vitamin C. Most recent works [91,92] show that fatty acid esters of ascorbic acid at either 6-or both 5-and 6-positions including the 5,6-erythrobyl dipalmitate deriwtive were almost as effective as the parent ascorbic acid as the chain-breaking antioxidant for linoleate in homogeneous solution, whereas those having an ester group at the 2-position did not exhibit the same property. Furthermore, the antioxidant efficiency of these esters was parallel to their reactivity towards galvinoxyl [93].…”
Section: Antioxidant Synergism Of Vitamin C and Vitamin Ementioning
confidence: 62%
“…Esterification on the 2-position is said to destroy its antioxidant activity (23), and esterification could allow it to elute with pure corn oil TAG during alumina purification. Ascorbate esters may be deacylated by sodium methoxide treatment, so we added ascorbic acid (0.2-9 ppm) and ascorbyl 6-palmitate (0.4-21 ppm) to natural corn oil to examine their effect on oxidative stability in the presence of naturally occurring trace metal ions.…”
Section: Figmentioning
confidence: 99%
“…Our results do not distinguish between other possibilities; for example, electron transfer from ascorbate, 2, to peroxyls followed by hydrogen-ion transfer would be equivalent overall to hydrogen-atom abstraction from 2 by peroxyls. W e also note that our interpretation does not account for the rather surprising finding that ascorbic acid with an ester group at the 2-position is reported not to act as an antioxidant in the oxidation of methyl linoleate in homogeneous solution (20). It is possible that a steric effect may be operating to inhibit the attack of linoleoyl peroxyl at the 3-position when position 2 is occupied by a fatty acid ester.…”
Section: Discussionmentioning
confidence: 58%
“…However, ascorbic acid has about the same reactivity as 6-steryl ascorbate with a vitamin E radical in solution, whereas the ascorbic ester substituted at the 2 and 6 positions was only 0.01 times as reactive as ascorbic acid (19). Derivatives having an ester group at position 2 were reported by Niki and co-workers (20) to not act '~u t h o r to whom correspondence may be addressed as antioxidants in homogeneous solution, suggesting that the enolic 2-OH is the hydrogen donor in inhibition reactions. However, others report that the 2-0-alkylascorbic acids (21) or 3-0-alkylascorbic acids (22) exhibit potent inhibition of lipid peroxidation in rat brain homogenates, indicating that both enolic OH groups can act as H-atom donors.…”
Section: Introductionmentioning
confidence: 92%